A Comparative Analysis of the Conversational Elements in S. T. Coleridge’s ‘Frost At Midnight’ and Badr Shakir Al-Sayyab’s ‘ Marha Ghailan’ - Taymaa Hussein Kheirbek (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2021)
The conversation poem is a genre of poetry mostly associated with Samuel Taylor Coleridge. It is usually characterized by being personal, emotional in nature, and often drawing on real events from the poet's life. This paper presents a comparative study of the conversational elements in S. T. Coleridge’s ‘Frost at Midnight’ and Badr Shaker Al-Sayyab’s ‘Marha Ghailan’. Similarity in focus, content, and style are going to be studied. In addition to that, certain points are going to be discussed and compared like; the minimalistic setting, the subjective experiences of both poets, the role of nature, the use of religion and myths, and the role given to the conversational partners.